To identify two equations that form a system with one solution (which means they have different slopes), we'll convert any equations that aren't already in the \( y = mx + b \) format.
Let's rewrite each equation in the \( y = mx + b \) format when necessary:
-
\( y = 5x - 4 \) (already in the correct format)
-
\( y = -2x + 3 \) (already in the correct format)
-
\( y = 3x + 1 \) (already in the correct format)
-
\( 2y = 6x + 2 \)
Dividing everything by 2: \[ y = 3x + 1 \] (This is equivalent to equation 3 and does not form a different slope.)
-
\( y - 5x = 2 \)
Rearranging gives: \[ y = 5x + 2 \]
-
\( y - 4x + 1 = 0 \)
Rearranging gives: \[ y = 4x - 1 \]
Now let's summarize the equations:
- \( y = 5x - 4 \) (slope = 5)
- \( y = -2x + 3 \) (slope = -2)
- \( y = 3x + 1 \) (slope = 3)
- \( y = 3x + 1 \) (slope = 3, equivalent to equation 3)
- \( y = 5x + 2 \) (slope = 5)
- \( y = 4x - 1 \) (slope = 4)
Now we can see the slopes clearly:
- Equation 1: slope = 5
- Equation 2: slope = -2
- Equation 3: slope = 3
- Equation 5: slope = 5
- Equation 6: slope = 4
To form a system with one solution, we must choose equations with different slopes.
Possible pairs with different slopes:
-
Equations 1 and 2:
- \( y = 5x - 4 \) and \( y = -2x + 3 \)
-
Equations 2 and 6:
- \( y = -2x + 3 \) and \( y = 4x - 1 \)
-
Equations 2 and 3:
- \( y = -2x + 3 \) and \( y = 3x + 1 \)
Thus, one example of a system with one solution is:
- \( y = 5x - 4 \)
- \( y = -2x + 3 \)
These two equations have different slopes and will intersect at one point (one solution).